Outcome of Dengue Fever Treated with Homeopathy Medicine: A Prospective Study - Amin, Md Ruhul; Hasan, Nazmul; Hashem Bhuyan, Mohammad Abul; Mashiusjaman, Md; Rahman, Ziaur; Jubayer, Shamim; Al Mamun, Mohammad Abdullah (Bioresearch Communications, 2025)
Background: Dengue is the most common arthropod-borne viral disease presented with various symptoms like fever, muscle pain, joint pain, and as well as asymptomatic cases. It may also cause potentially fatal sickness and danger signs with severe abdominal pain, vomiting, bleeding from gums and nose, hematuria and hematochezia. Homeopathy is a symptomatic treatment system, which may reduce symptoms quickly when appropriate remedy is applied on the basis of individualization. Present study conducted to determine the clinical sign and symptoms of dengue fever and to observe the patient’s condition after taking homeopathy medicine. Methods: This present observational prospective study was conducted in Outpatients’ Department (OPD) of Govt. Homeopathic Medical College and Hospital, Mirpur, Dhaka between the periods of August-October’2023. A total of 99 patients of dengue fever were included in the study. Data were collected by face-to-face interview of the patients and follow-up done on 3rd, 6th and 9th day with appropriate investigations required for the follow-up. All patients were treated with homeopathic medicine. Result: Mean±SD of age of the patients was 27.7±9.4 and range was from 11-60 years. Among the patients 73.74% were male and 26.36% were female. All patients were presented with fever. Other presenting symptoms, ‘headache’ ‘myalgia’, ‘joint pain’, ‘abdominal pain’, vomiting and pain in the retro-orbital region’ were, 91.92%, 87.88%, 84.85%, 73.74%, 17% and 85.86% respectively. About 46.46% of patients experienced diarrhea, and 21.21% presented with bleeding from different sites. Mean±SD of Platelet was 148333.3±29642.31, 137888.9±118516.2 and 177111.1±49194.5, respectively on 3rd, 6th, and 9th day of fever. In this study mean±SD of HCT was 40.67±4.67, 41.62±5.59 and 41.23±3.83, respectively on 3rd, 6th and 9th day of fever. Among the study dengue patients, 3.03% were diagnosed with dengue hemorrhagic fever (DHF). Hemoglobin was 13.63±1.49 gm/dl, 13.6±1.72 gm/dl, and 13.98±1.57 gm/dl on the 3rd, 6th and 9th day, respectively. None of the patients faced shock syndrome of dengue fever. Conclusion. Vector born disease, Dengue may be treated with Homeopathy medicine. However, further large-scale studies are needed to consider its effectiveness in Dengue fever. Bioresearch Commu. 11(2): 1869-1873, 2025 (July)